A case report of a patient with blue rubber bleb nevus syndrome presenting with severe gastrointestinal bleeding - Siwiński, Paweł; Sobolewska-Włodarczyk, Aleksandra; Włodarczyk, Marcin; Stec-Michalska, Krystyna; Wiśniewska-Jarosińska, Maria (Journal of Medical Science, 2017)
Blue rubber bleb nevus syndrome (BRBNS) is an uncommon condition presenting with multiple cutaneous and visceral vascular malformations, predominantly in the gastrointestinal (GI) tract. Typical skin lesion consists of a blue, soft tumor of a rubber like cohesiveness, that is easily compressible and refills slowly on release of pressure. The GI lesions are more clinically relevant, as they may induce chronic bleeding or even life threatening massive hemorrhages. This report presents a case of BRBNS diagnosed in a 52-year-old male with signs of lower gastrointestinal bleeding. The patient presented with melena, fatigue and severe anemia, which were treated by numerous blood transfusions and iron supplementation. Multiple vascular changes were visualized in the small intestine. A typical skin lesion was also present in the skin. Additionally, this report describes the clinical aspects of the syndrome, diagnostic preferences, as well as possible critical complications.